Market basket analysis - Mendes, António Miguel Lobo Machado Teixeira (2020)
The purpose of this thesis is to identify relevant relationships between Recheio’s product categories with the aim of increasing the firm’s sales. A Market Basket Analysis was performed to unveil these relationshipswhere atotal of 53 different Association Ruleswere generated. By including the obtained results in its order placement process, Recheio will be able to capture more value from each order by making sustained suggestions to its customers regarding what additional products to buy.